Strengthening Ecotheological Education in Enhancing Environmental Piety (Research at SMP Daarut Tauhiid Boarding School) - Mada Sumringah Sari; Rosihon Anwar; Supiana Supiana; Karman Karman (MASI Mandiri Edukasi, 2026)
Ecotheological education is designed to foster environmental piety by integrating religious values with ecological responsibility. However, its implementation in practice has not been fully effective, indicating the need for more targeted educational strategies and optimal supervision to achieve comprehensive environmental piety. This study aims to describe and analyse the strengthening of ecotheological education in improving environmental piety at SMP Daarut Tauhiid Boarding School. This research employs a descriptive qualitative approach, focusing on the process of strengthening ecotheological education. Data were collected through observation, in-depth interviews, and documentation studies involving the school principal, teachers, and students. The findings reveal that strengthening ecotheological education enhances students’ environmental awareness and positive attitudes, as well as their ability to identify and provide appropriate solutions to environmental problems. This study highlights the importance of strengthening ecotheological education as an effective strategy for fostering environmental piety and offers a model for implementing it that can be sustainably applied within the school environment.